Evaluation of the flammability and thermal properties of a new flame retardant coating applied on polyester fabric - A.A. Younis (Egyptian Journal of Petroleum)
The objective of this research was to investigate the effect of non-durable flame retardant (NDFR) coating of samples of polyester fabric untreated and treated with UV/Ozone for different periods. For this purpose, these samples were tested by Fourier transform infrared (FTIR) spectroscopy, thermal analysis tests as thermo-gravimetric analysis (TGA) and differential scanning calorimeter (DSC). The ignition test was applied using limiting oxygen index (LOI), flame chamber (UL/94). Results indicated that both AZ2 (dried at room temperature) and AZ8–12 (dried at 80 °C for 30 min after coating with non-durable fire retardant (NDFR) coating) polyester samples have significantly decreased the rate of burning and increased the limiting oxygen index.